THE IMPORTANCE OF INDIVIDUAL TESTS IN THE DEVELOPMENT OF CREATIVE ABILITIES IN STUDENTS (Conference Zone, 2021)
Individual testing is extremely important for enhancing the students creativity that is widely accepted as being an important outcome of schooling. Yet there are many different views about what it is, how best it can be cultivated in young people and whether or how it should be assessed. And in many national curricula creativity is only implicitly acknowledged and seldom precisely defined. This article discusses the efficacy of cognitive ability tests in the identification of subject specific abilities and creativity of the students.And suggests a theoretical underpinning for defining and assessing creativity along with a number of practical suggestions as to how creativity can be developed and tracked for students